The effects of endurance training on muscle fibre types and enzyme activities - Taylor, A. W.; Bachman, L. (Canadian Journal of Applied Physiology, 1999)
Practitioners and scientists have demonstrated great interest in the physiological and biochemical effects of endurance training on the results of the marathon run. It is well documented that athletes with a large proportion of slow twitch and fast twitch aerobic skeletal muscle fibre, high metabolic enzyme activities and concentrations, large mitochondria concentration and, of course, the ability to increase the power output generated for a given rate of oxygen consumption and energy expenditure, are generally highly successful distance runners. Aerobic and endurance training have been shown to bring about significant adaptations to the skeletal muscle and its inclusions as well as to the delivery system. In particular, enzyme activity levels are readily mutable, mitochondrial concentrations increase, and some evidence suggests that the fibre distribution is changed. This article briefly reports on changes in skeletal muscle brought about by endurance training and those changes that appear most effective in yielding success in endurance events.